Evaluación del lumen de luces, LEDs para el control físico de lepidoptera gelechiidae en invernaderos de tomate riñón (lycopersicon esculentum mill) - Caluguillin Caluguillin, Vladimir Isaías (2022)
This research consisted of evaluating the relationship between the lumen of LED lights and the incidence of captures of lepidoptera considered pests. The quantitative experimental field method was used, and completely randomized design, where three objectives were addressed: First, it was analyzed by means of a survey on the presence of lepidoptera in kidney tomato producers (Lycopersicon esculentum Mill), confirming the presence in addition to economic losses due to crop damage. Then the network of traps was established at different lumens 1320 lm, 800 lm, 400 lm and 200 lm inside the greenhouses, and the number of lepidoptera captured per experimental unit for 90 days was counted per night, supported by statistical tests (ANOVA and Tukey) showing that the 1320 lm lumen had a significant effect as a physical control, with an average of 14.5 captures, establishing itself as the most effective in relation to the application of 200 lm with an average of 1.5, being the trap that quantified the lowest capture between the treatments. And finally, the results obtained in the research were disclosed to the producers through citizen participation mechanisms, in this way the use of LEDs as physical control in the productions was disseminated, which was carried out in the community session room. In short, the greater the lumen, the greater the capture of lepidoptera in greenhouses